Analisis Vegetasi Tumbuhan Bawah Pada Lahan Bekas Tambang Batubara Pt. Allied Indo Coal Jaya Kota Sawahlunto - Fitri, Zakiatil; Solfiyeni, Solfiyeni (Universitas Andalas, 2024)
PT. Allied Indo Coal Jaya Sawahlunto City is a coal mining area. Research on Analysis of Understorey Vegetation on Ex-CoalMining Land at PT. AICJ has been carried out in June-August 2021. This study aims to determine the composition and structureof understorey vegetation. Vegetation analysis was carried out using the quadratic method with plots laid by purposive sampling.The plots were made of 15 plots on ex-coal mining land in 1990 and 2007 with a plot size of 2x2 m each. Based on the results ofthe former coal mining area in 1990, it was found that the Asteraceae family was dominant (24.35%), Chromolaena odorata (L.)R.M.King & H.Rob. as the highest INP (18.73%), high diversity index (3.153%), and high evenness index (0.946). In the ex-coalmining area in 2007, the Poaceae family was found to be dominant (39.01%), Paspalum conjugatum P.J. Bergius with the highestINP (40.67%), moderate diversity index (2.861), and high evenness index (0.912). The similarity index between the two locationsis quite high,namely70.50%.